Initial T cell frequency dictates memory CD8+ T cell lineage commitment. - Marzo, A; Klonowski, K; Le Bon, A; Borrow, P; Tough, D; Lefrançois, L (2005)
Memory T cells can be divided into central memory T cell (T(CM) cell) and effector memory T cell (T(EM) cell) subsets based on homing characteristics and effector functions. Whether T(EM) and T(CM) cells represent interconnected or distinct lineages is unclear, although the present paradigm suggests that T(EM) and T(CM) cells follow a linear differentiation pathway from naive T cells to effector T cells to T(EM) cells to T(CM) cells. We show here that naive T cell precursor frequency profoundly influenced the pathway along which CD8+ memory T cells developed. At low precursor frequency, those T(EM) cells generated represented a stable cell lineage that failed to further differentiate into T(CM) cells. These findings do not adhere to the present dogma regarding memory T cell generation and provide a means for identifying factors controlling memory T cell lineage commitment.